Business Judgment Rule: Prinsip Perlindungan Bagi Direksi dalam Pengambilan Keputusan Bisnis Perusahaan - Purnama Hadi Kusuma; Usnadi Usnadi; Abdul Rahman Salman Faris (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2026)
Business judgment rule (BJR) is a principle of protecting directors from suboptimal business decisions that result in company losses. The purpose of this study is to analyze and to explore the legal provisions of BJR and its application principles, which are often related to several cases of directors of companies in making business decisions. The following study uses a normative research method (normative legal research) with a descriptive analytical nature that examines secondary data sources obtained from reading library materials which are finally analyzed qualitatively. Regulations related to BJR can be found in the provisions of the Limited Company Law, the Financial Services Authority Regulation for public companies, and the BUMN Law, as well as the Regulation of the Minister of BUMN in regulating BJR and the application of the principles good corporate governance within the scope of state-owned enterprises. The principle of BJR protection for company directors applies as long as they can prove themselves in managing the company within the corridor fiduciary duty, duty of care, duty of skill, duty of loyalty, and not involved in the practice conflict of interest.